A microwave-absorbing honeycomb core material and a microwave-absorbing honeycomb core sandwich structure

By using the surface metallic and hollow glass micro beads as a suction material in the honeycomb expiration structure, the problem of insufficient ripple width and low -frequency absorbing performance in existing technologies, and realizing the while absorbing low -frequency and high -frequency electromagnetic waves.

CN114670526BActive Publication Date: 2025-01-28LUOYANG INST OF CUTTING EDGE TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202011556668.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2020-12-24
Publication Date
2025-01-28
Estimated Expiration
2040-12-24

AI Technical Summary

Technical Problem

The existing honeycomb sandwich structure has a narrow wave absorbance bandwidth and insufficient low-frequency absorbance performance.

Method used

The surface metal -based hollow glass micro beads are used as a suction material. The metal layer is covered on the hollow glass micro beads, and it is loaded on the honeycomb matrix to effectively avoid metal settlement and achieve uniform distribution.

Benefits of technology

The absorption rate of low -frequency and high -frequency electromagnetic waves has been improved, the width of the wave absorption is expanded, and the overall suction performance is enhanced.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention provides a wave-absorbing honeycomb core material and a wave-absorbing honeycomb core sandwich structure. The wave-absorbing honeycomb core material includes a honeycomb matrix, a resin bonding portion and a wave-absorbing material, wherein the resin bonding portion fixes the wave-absorbing material on the honeycomb matrix, and the wave-absorbing material is a surface-metallized hollow glass microsphere. The present application uses metallized hollow glass microspheres to replace the dielectric material and ferromagnetic material commonly used in wave honeycomb core materials in the prior art as wave absorbers. The metal-coated hollow glass microspheres have the advantages of low density and large specific surface area, and the hollow structure formed by loading the metal on the surface of the hollow glass microspheres has a thin metal coating on the one hand, which can effectively reduce the skin effect caused by the metal material, so that the electromagnetic waves can enter the interior of the wave-absorbing material, effectively improving the magnetic loss; on the other hand, after the electromagnetic waves enter the hollow microspheres, they will be reflected multiple times inside, further improving the absorption rate of the electromagnetic waves, thereby effectively improving the low-frequency wave absorbing performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of wave-absorbing materials, and in particular to a wave-absorbing honeycomb core material and a wave-absorbing honeycomb core sandwich structure. Background Art

[0002] There are many different structural forms of structural stealth materials, such as laminated structures, laminated composite structures, and sandwich structures. Among them, sandwich composite materials are a typical lightweight, high-strength, high-rigidity structural design solution, which organically combines the high strength and high modulus of the panel with the low density and high rigidity of the core, and has extremely important application value in aerospace and other fields.

[0003] Stealth design and manufacturing of sandwich structures is a new technology today, and foam sandwich and honeycomb sandwich are the two most important forms. In the preparation of the wave-absorbing honeycomb sandwich, the absorbent is evenly dispersed in the resin solution to obtain the wave-absorbing resin glue, and the wave-absorbing resin glue is impregnated into the honeycomb core multiple times. After curing, the wave-absorbing honeycomb sandwich is obtained, and then the wave-absorbing honeycomb sandwich is bonded with the wave-transmitting skin, the reflective layer, etc. to obtain a honeycomb sandwich structure wave-absorbing composite material. The absorbent is mostly dielectric absorbent such as carbon black, graphene, and carbon nanotubes. This type of absorbent has a low density and can be evenly dispersed in the glue. The wave-absorbing bandwidth of the composite material can be broadened through a reasonable gradient design, but the low-frequency wave-absorbing performance is often not ideal. When ferromagnetic materials are used as absorbents, the absorbent density is large. During the solvent dispersion, coating, and impregnation process, the absorbent is prone to sedimentation, which is limited in the preparation process and the wave-absorbing effect is not ideal. Summary of the invention

[0004] The main purpose of the present invention is to provide a wave-absorbing honeycomb core material and a wave-absorbing honeycomb core sandwich structure to solve the problems of narrow wave-absorbing bandwidth and insufficient low-frequency wave-absorbing performance of the honeycomb sandwich structure in the prior art.

[0005] In order to achieve the above-mentioned purpose, according to one aspect of the present invention, a wave honeycomb core material is provided, which comprises a honeycomb matrix, a resin bonding part and an absorbing material, wherein the resin bonding part fixes the absorbing material on the honeycomb matrix, and the absorbing material is a surface metallized hollow glass microsphere.

[0006] Furthermore, the surface metallized hollow glass microspheres are selected from any one or more of Ni-plated hollow glass microspheres, Fe-plated hollow glass microspheres, and Co-plated hollow glass microspheres, and the thickness of the metal layer is preferably 0.02-1.

[0007] Furthermore, the D90 of the above-mentioned absorbing material is between 5 and 15 μm.

[0008] Furthermore, in the above-mentioned absorbing honeycomb core material, the weight ratio of the honeycomb matrix, the resin bonding part and the absorbing material is 20-40:30-50:10-20.

[0009] Furthermore, the resin bonding portion is formed by curing one or more of hot-melt epoxy resin, hot-melt phenolic resin or hot-melt bismaleimide resin.

[0010] Furthermore, the honeycomb matrix is ​​an aramid paper honeycomb.

[0011] According to another aspect of the present invention, there is provided an absorbing honeycomb core sandwich structure, comprising a wave-transmitting layer, an absorbing honeycomb core layer and a reflecting layer bonded in sequence, wherein the absorbing honeycomb core layer is any one of the above-mentioned absorbing honeycomb core materials, and preferably the thickness of the absorbing honeycomb core layer is 5 to 20 mm.

[0012] Furthermore, the thickness of the above-mentioned wave-transmitting layer is 0.2-1.0 mm, and the wave-transmitting layer includes a first fiber matrix and a first resin loaded on the first fiber matrix. Preferably, the weight content of the first resin in the wave-transmitting layer is 33%-45%, and preferably the fiber matrix is ​​quartz fiber or glass fiber, and the first resin is epoxy resin or cyanate ester.

[0013] Furthermore, the above-mentioned absorbing honeycomb core sandwich structure also includes an absorbing layer bonded between the absorbing honeycomb core layer and the reflecting layer. The thickness of the absorbing layer is preferably 1.0 to 3.0 mm. The absorbing layer includes a second fiber matrix, a second resin loaded on the second fiber matrix, and an absorbing agent. The weight ratio of the second fiber matrix, the second resin and the absorbing agent is 15 to 30:15 to 30:40 to 70. The second resin is preferably a hot-melt epoxy resin or a bismaleimide resin. The second fiber matrix is ​​preferably quartz fiber or aramid fiber. The absorbing agent is preferably a magnetic medium type absorbing agent. The D90 of the magnetic medium type absorbing agent is preferably between 1 and 10 μm. The magnetic medium type absorbing agent preferably includes any one or more of ferrite, carbonyl iron powder and ultrafine metal powder.

[0014] Furthermore, the thickness of the above-mentioned reflective layer is 0.2-0.6 mm, the reflective layer comprises carbon fiber and epoxy resin loaded on the carbon fiber, and the weight content of the epoxy resin in the reflective layer is 33-50%.

[0015] By applying the technical solution of the present invention and using metallized hollow glass microspheres as absorbing materials, on the one hand, the skin effect caused by metal materials can be effectively reduced, so that electromagnetic waves can enter the interior of the absorbing materials, effectively improving the magnetic loss; on the other hand, after the electromagnetic waves enter the hollow microspheres, they will be reflected multiple times inside, further improving the absorption rate of electromagnetic waves, thereby effectively improving the low-frequency absorbing performance. At the same time, after the metal layer is coated on the hollow glass microspheres as an absorbing material, when the absorbing material is loaded on the honeycomb substrate, the sedimentation of the metal is effectively avoided, and the effect of being distributed as evenly as possible on the honeycomb carrier is achieved. In summary, the absorbing honeycomb core material of the present application utilizes evenly distributed absorbing materials and honeycomb carriers to achieve the simultaneous absorption of low-frequency waves and high-frequency waves. DETAILED DESCRIPTION

[0016] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below in conjunction with the embodiments.

[0017] As described in the background technology of this application, the low-frequency wave absorption performance of dielectric absorbers such as graphene and carbon nanotubes is not ideal. When ferromagnetic materials are used as absorbers, the absorber density is large. During solvent dispersion, coating and impregnation, the absorber is prone to sedimentation, which is limited in the preparation process and the wave absorption effect is not ideal. In addition, for metal absorbers in the prior art, they are generally solid particles with larger particle size (3 to 5 μm or higher) or flaky particles with thicker thickness (>1 μm), so skin effect will occur, that is, under the alternating electric field, current will be generated on the surface of the metal absorber, and the current will form eddy current. When the incident electromagnetic wave is incident, reflection will occur, so that fewer electromagnetic waves enter the material, reducing electromagnetic losses and deteriorating the wave absorption performance. It can be seen that the honeycomb sandwich structure in the prior art has the problems of narrow wave absorption bandwidth and insufficient low-frequency wave absorption performance. In order to solve the above problems, the present application provides a wave absorbing honeycomb core material and a wave absorbing honeycomb core sandwich structure.

[0018] In a typical embodiment of the present application, an absorbing honeycomb core material is provided, including a honeycomb matrix, a resin bonding portion and an absorbing material, wherein the resin bonding portion fixes the absorbing material on the honeycomb matrix, and the absorbing material is a surface metallized hollow glass microsphere.

[0019] The present application uses metallized hollow glass microspheres to replace the dielectric materials and ferromagnetic materials commonly used in the prior art for wave honeycomb core materials as wave absorbers. Metal-coated hollow glass microspheres have the advantages of low density and large specific surface area, and the hollow structure formed by loading the metal on the surface of the hollow glass microspheres, on the one hand, the metal coating is thin, which can effectively reduce the skin effect caused by the metal material, so that the electromagnetic waves can enter the interior of the wave absorbing material, effectively improving the magnetic loss; on the other hand, after the electromagnetic waves enter the hollow microspheres, they will be reflected multiple times inside, further improving the absorption rate of the electromagnetic waves, and thus effectively improving the low-frequency wave absorbing performance. At the same time, after the metal layer is coated on the hollow glass microspheres as a wave absorbing material, when the wave absorbing material is loaded on the honeycomb substrate, the sedimentation of the metal is effectively avoided, and the effect of being distributed as evenly as possible on the honeycomb carrier is achieved. In summary, the wave absorbing honeycomb core material of the present application utilizes evenly distributed wave absorbing materials and honeycomb carriers to achieve the simultaneous absorption of low-frequency waves and high-frequency waves.

[0020] The metal coating of the present application can be selected from metal materials commonly used for wave absorption in the prior art. Preferably, the surface metallized hollow glass microspheres are selected from any one or more of Ni-plated hollow glass microspheres, Fe-plated hollow glass microspheres, and Co-plated hollow glass microspheres. Ni, Fe, and Co all have good electrical conductivity and ferromagnetism, so they can effectively improve the wave absorption performance of the wave absorbing material. In order to further control the skin effect of the metal material, the thickness of the metal layer is preferably 0.02 to 1 μm.

[0021] In order to make the absorbing material more dispersed in the honeycomb matrix, the D90 of the absorbing material is preferably between 5 and 15 μm. The absorbing material with the above particle size range is easy to disperse in the honeycomb matrix and easy to bond.

[0022] In one embodiment, in the above-mentioned absorbing honeycomb core material, the weight ratio of the honeycomb matrix, the resin bonding part and the absorbing material is preferably 20-40:30-50:10-20. By limiting the above-mentioned weight ratio, the characteristics of the honeycomb core material being light and having excellent absorbing performance can be taken into account. At the same time, the specific ratio between the resin bonding part and the absorbing material can enable the absorbing material to be stably bonded to the surface of the honeycomb matrix, thereby improving the structural stability. In summary, by further limiting the weight ratio between the components, the absorbing honeycomb core material has both light weight and excellent absorbing performance, while also improving its structural stability.

[0023] The resin bonding part of the present application can select various adhesives commonly used in the prior art for bonding absorbing materials. In order to adapt to the physical performance characteristics of the surface metallized hollow glass microspheres of the present application, the resin bonding part is preferably solidified by one or more of hot-melt epoxy resin, hot-melt phenolic resin or hot-melt bismaleimide resin. The above resin is solid or semi-solid at room temperature, and can be softened to a molten state after being heated, and a dry method can be used to prepare prepreg. In addition, the above resin contains a latent curing agent, which can be directly cured at high temperature, and has good processing performance and good adhesion, and can firmly bond the metallized hollow glass microspheres to the surface of the honeycomb substrate.

[0024] Any material with a honeycomb structure in the prior art can be considered as the honeycomb matrix of the present application. In order to meet the requirements of light weight, high strength, better synergy with surface metallized hollow glass microspheres, and meet the needs of various application scenarios, the above-mentioned honeycomb matrix is ​​preferably an aramid paper honeycomb.

[0025] The preparation method of the above-mentioned absorbing honeycomb core material of the present application can refer to the preparation method of the absorbing honeycomb core material in the prior art, such as by impregnation, etc. In order to make it more convenient for those skilled in the art to prepare the absorbing honeycomb core material, a preparation method is exemplified as follows:

[0026] The hot-melt resin is dissolved in a solvent, a dispersant and surface metallized hollow glass microbeads are added, and the mixture is mechanically stirred to obtain a microwave-absorbing resin glue solution; the glue solution is applied to the honeycomb core for multiple times, and the honeycomb core is weighed after drying until the target weight gain is reached; the impregnated honeycomb core is placed in an oven for curing to obtain a microwave-absorbing honeycomb core material.

[0027] Those skilled in the art should understand that the above preparation method is only an exemplary description and does not mean that the wave-absorbing honeycomb core material of the present application can only be obtained by the above method.

[0028] In another typical embodiment of the present application, an absorbing honeycomb core sandwich structure is provided, comprising a wave-transmitting layer, a wave-absorbing honeycomb core layer and a reflective layer bonded in sequence, the wave-absorbing honeycomb core layer is any one of the above-mentioned wave-absorbing honeycomb core materials, and preferably the thickness of the wave-absorbing honeycomb core layer is 5 to 20 mm.

[0029] By using the absorbing honeycomb core material of the present application, in addition to meeting the requirement of the absorbing honeycomb core sandwich structure for the light weight of the absorbing honeycomb core layer, metallized hollow glass microspheres with low density and large specific surface area are used as absorbers to achieve low-frequency and broadband absorbing performances. Therefore, the absorbing performance of the absorbing honeycomb core sandwich structure having the absorbing honeycomb core material is effectively improved.

[0030] There are many effective design schemes for the wave-transmitting layer in the prior art. In order to cooperate with the wave-absorbing honeycomb core material of the present application to achieve a synergistic effect, the wave-transmitting layer is preferably 0.2-1.0 mm thick, and the wave-transmitting layer includes a first fiber matrix and a first resin loaded on the first fiber matrix. The weight content of the first resin in the wave-transmitting layer is preferably 33%-45%, and the fiber matrix is ​​preferably quartz fiber or glass fiber, and the first resin is epoxy resin or cyanate ester. The wave-transmitting layer has strong rigidity and strength on the one hand, which can protect the wave-absorbing honeycomb core material, and on the other hand, allows the incident electromagnetic waves to enter the wave-absorbing honeycomb core material and the wave-absorbing layer as much as possible and be fully absorbed.

[0031] In one embodiment, the absorbing honeycomb core sandwich structure preferably further includes an absorbing layer bonded between the absorbing honeycomb core layer and the reflecting layer. It is further preferred that the thickness of the absorbing layer is 1.0 to 3.0 mm. The absorbing layer includes a second fiber matrix, a second resin loaded on the second fiber matrix, and an absorbent. The weight ratio of the second fiber matrix, the second resin, and the absorbent is 15 to 30:15 to 30:40 to 70. The second resin is preferably a hot-melt epoxy resin or a bismaleimide resin. The second fiber matrix is ​​preferably a quartz fiber or an aramid fiber. The absorbent is preferably a magnetic medium absorbent. The D90 of the magnetic medium absorbent is preferably between 1 and 10 μm. The magnetic medium absorbent includes any one or more of ferrite, carbonyl iron powder, and ultrafine metal powder. The absorbing layer as a supplement to the absorbing honeycomb can improve the absorbing performance of the entire sandwich structure. Therefore, conventional absorbing layers in the prior art that can achieve the above-mentioned absorbing effect can be considered for application in this application. The wave-absorbing layer of the present application can further enhance the wave-absorbing effect of the wave-absorbing honeycomb core sandwich structure, so that the incident electromagnetic waves can be absorbed as much as possible.

[0032] The function of the above-mentioned reflective layer is mainly to reflect the unabsorbed frequency band to the absorbing honeycomb core layer to further absorb it. Therefore, any conventional reflective layer in the prior art that can achieve the above-mentioned reflection effect can be considered for application in this application. In order to cooperate with the absorbing honeycomb core material of this application to achieve a synergistic effect, the thickness of the reflective layer is 0.2-0.6 mm. The reflective layer includes carbon fiber and epoxy resin loaded on the carbon fiber, and the weight content of the epoxy resin in the reflective layer is 33-50%. On the one hand, the above-mentioned reflective layer has strong rigidity and strength, which can protect the absorbing honeycomb core material. On the other hand, it can reflect the electromagnetic waves that are not absorbed by the absorbing layer and the absorbing honeycomb core layer back to the absorbing layer and the absorbing honeycomb core layer, so that the electromagnetic waves can be absorbed to the maximum extent.

[0033] The adhesive material used for bonding the various layers in the above-mentioned wave-absorbing honeycomb core sandwich structure can be the adhesive material commonly used in the wave-absorbing honeycomb sandwich structure, which will not be described in detail here.

[0034] The beneficial effects of the present invention are further illustrated below in conjunction with the embodiments.

[0035] Example 1

[0036] (1) A hot-melt epoxy resin is dissolved in N,N-dimethylacetamide solvent, and Ni-plated hollow glass microspheres (the particle size D90 of the Ni-plated hollow glass microspheres is 10 μm, and the average thickness of the nickel layer on the surface of the hollow microspheres is 0.5 μm, as a microwave absorbing material) are added, and mechanical stirring is performed for 60 minutes to obtain a microwave absorbing resin glue solution; the glue solution is repeatedly applied to an aramid paper honeycomb core with a thickness of 5 mm, and the core is weighed after drying until the target weight gain is reached; the impregnated aramid paper honeycomb core is placed in an oven and cured at 180°C for 120 minutes to obtain a microwave absorbing honeycomb core, which includes 30 parts of honeycomb, 10 parts of absorbing material, and 40 parts of resin.

[0037] (2) The wave-transmitting layer, the wave-absorbing honeycomb core obtained in the above step (1), the wave-absorbing layer and the reflective layer are bonded and cured from top to bottom by a structural adhesive film to obtain a wave-absorbing honeycomb core sandwich structure. The wave-transmitting layer is a quartz fiber reinforced cyanate ester composite material with a resin content of 38% and a thickness of 0.6 mm. The fiber matrix of the wave-absorbing layer is a quartz fiber reinforced bismaleimide resin composite material with a thickness of 2.4 mm, and the dispersed absorbent is an ultrafine iron-aluminum-silicon alloy powder with a particle size D90 of 8 μm. The components of the wave-absorbing layer are calculated by weight: 20 parts of resin, 20 parts of fiber, and 45 parts of absorbent. The reflective layer is a carbon fiber reinforced epoxy resin-based composite material with a resin content of 40% and a thickness of 0.4 mm.

[0038] Example 2

[0039] (1) A hot-melt phenolic resin is dissolved in an ethanol solvent, and Fe-plated hollow glass microspheres (the particle size D90 of the Fe-plated hollow glass microspheres is 5 μm, and the average thickness of the iron layer on the surface of the hollow microspheres is 0.8 μm, as a wave-absorbing material) are added, and mechanical stirring is performed for 60 minutes to obtain a wave-absorbing resin glue solution; the glue solution is repeatedly applied to an aramid paper honeycomb core with a thickness of 10 mm, and the core is weighed after drying until the target weight gain is reached; the impregnated aramid paper honeycomb core is placed in an oven and cured at 180° C. for 120 minutes to obtain a wave-absorbing honeycomb core, wherein the wave-absorbing honeycomb core includes 30 parts of honeycomb, 10 parts of wave-absorbing material, and 40 parts of resin.

[0040] (2) The wave-transmitting layer, the wave-absorbing honeycomb core obtained in the above step (1), the wave-absorbing layer and the reflective layer are bonded and cured from top to bottom by a structural adhesive film to obtain a wave-absorbing honeycomb core sandwich structure. The wave-transmitting layer is a glass fiber reinforced epoxy resin composite material with a resin content of 33% and a thickness of 1.0 mm. The fiber matrix of the wave-absorbing layer is an aramid fiber reinforced epoxy resin composite material with a thickness of 3.0 mm, and the dispersed absorbent is carbonyl iron powder with a particle size D90 of 5 μm. The components of the wave-absorbing layer are calculated by weight: 30 parts of resin, 30 parts of fiber, and 60 parts of absorbent. The reflective layer is a carbon fiber reinforced epoxy resin-based composite material with a resin content of 50% and a thickness of 0.6 mm.

[0041] Example 3

[0042] (1) A hot-melt bismaleimide resin was dissolved in an acetone solvent, and Co-plated hollow glass microspheres (the particle size D90 of the Co-plated hollow glass microspheres was 15 μm, and the average thickness of the cobalt layer on the surface of the hollow microspheres was 0.9 μm, as a wave-absorbing material) were added, and mechanical stirring was performed for 60 min to obtain a wave-absorbing resin glue solution; the glue solution was repeatedly applied to an aramid paper honeycomb core with a thickness of 20 mm, and the core was weighed after drying until the target weight gain was reached; the impregnated aramid paper honeycomb core was placed in an oven and cured at 200°C for 240 min to obtain a wave-absorbing honeycomb core, which includes 20 parts of honeycomb, 15 parts of absorbing material, and 30 parts of resin.

[0043] (2) The wave-transmitting layer, the wave-absorbing honeycomb core obtained in the above step (1), the wave-absorbing layer and the reflective layer are bonded and cured from top to bottom by a structural adhesive film to obtain a wave-absorbing honeycomb core sandwich structure. The wave-transmitting layer is a quartz fiber reinforced cyanate ester composite material with a resin content of 45% and a thickness of 0.2 mm. The fiber matrix of the wave-absorbing layer is a quartz fiber reinforced bismaleimide resin-based composite material with a thickness of 1.5 mm, wherein the dispersed absorbent is ferrite with a particle size D90 of 10 μm. The components of the wave-absorbing layer are calculated by weight: 30 parts of resin, 15 parts of fiber, and 45 parts of absorbent. The reflective layer is a carbon fiber reinforced epoxy resin-based composite material with a resin content of 40% and a thickness of 0.2 mm.

[0044] Example 4

[0045] (1) A hot-melt epoxy resin is dissolved in N,N-dimethylacetamide solvent, and Co-plated hollow glass microspheres (the particle size D90 of the Co-plated hollow glass microspheres is 8 μm, and the average thickness of the cobalt layer on the surface of the hollow microspheres is 0.75 μm, as the absorbing material) are added, and mechanical stirring is performed for 60 minutes to obtain an absorbing resin glue solution; the glue solution is repeatedly applied to an aramid paper honeycomb core with a thickness of 15 mm, and the core is weighed after drying until the target weight gain is reached; the impregnated aramid paper honeycomb core is placed in an oven and cured at 180°C for 120 minutes to obtain an absorbing honeycomb core, wherein the absorbing honeycomb core includes 40 parts of honeycomb, 20 parts of absorbing material, and 50 parts of resin.

[0046] (2) The wave-transmitting layer, the wave-absorbing honeycomb core obtained in the above step (1), the wave-absorbing layer and the reflective layer are bonded and cured from top to bottom by a structural adhesive film to obtain a wave-absorbing honeycomb core sandwich structure. The wave-transmitting layer is a quartz fiber reinforced epoxy resin composite material with a resin content of 40% and a thickness of 0.5 mm. The fiber matrix of the wave-absorbing layer is a quartz fiber reinforced bismaleimide resin composite material with a thickness of 1.0 mm, and the dispersed absorbent used is an ultrafine iron-aluminum-silicon alloy powder with a particle size D90 of 1 μm. The components of the wave-absorbing layer are calculated by weight: 30 parts of resin, 25 parts of fiber, and 70 parts of absorbent. The reflective layer is a carbon fiber reinforced epoxy resin-based composite material with a resin content of 45% and a thickness of 0.3 mm.

[0047] Example 5 (1)

[0049] The hot-melt epoxy resin was dissolved in N, N-dimethylacetamide solvent, and Ni-plated hollow glass microspheres (the particle size D90 of the Ni-plated hollow glass microspheres was 10 μm, and the average thickness of the nickel layer on the surface of the hollow microspheres was 0.6 μm, as the absorbing material) were added, and mechanical stirring was performed for 60 minutes to obtain the absorbing resin glue solution; the glue solution was repeatedly coated and impregnated on an aramid paper honeycomb core with a thickness of 5 mm, and the core was weighed after drying until the target weight gain was reached; the impregnated aramid paper honeycomb core was placed in an oven and cured at 180°C for 120 minutes to obtain the absorbing honeycomb core, which includes 30 parts of honeycomb, 10 parts of absorbing material, and 40 parts of resin.

[0050] (2) The heat-pressed pot process is adopted to prepare the wave-transmitting layer, the wave-absorbing honeycomb core obtained in the above step (1), the wave-absorbing layer and the reflective layer, which are sequentially bonded and cured from top to bottom by a structural adhesive film to obtain a wave-absorbing honeycomb core sandwich structure. The wave-transmitting layer is a quartz fiber reinforced cyanate ester composite material with a resin content of 38% and a thickness of 0.6 mm. The fiber matrix of the wave-absorbing layer is a quartz fiber reinforced bismaleimide resin composite material with a thickness of 2.4 mm, wherein the dispersed absorbent is an ultrafine iron-aluminum-silicon alloy powder with a particle size D90 of 8 μm. The components of the wave-absorbing layer are calculated by weight: 15 parts of resin, 15 parts of fiber, and 40 parts of absorbent. The reflective layer has a resin content of 33% and a thickness of 0.4 mm.

[0051] Example 6

[0052] The hot-melt epoxy resin was dissolved in N, N-dimethylacetamide solvent, and Ni-plated hollow glass microspheres (the particle size D90 of the Ni-plated hollow glass microspheres was 10 μm, and the average thickness of the nickel layer on the surface of the hollow microspheres was 0.5 μm, as the absorbing material) were added, and mechanical stirring was performed for 60 minutes to obtain an absorbing resin glue solution; the glue solution was repeatedly coated and impregnated on an aramid paper honeycomb core with a thickness of 5 mm, and the core was weighed after drying until the target weight gain was reached; the impregnated aramid paper honeycomb core was placed in an oven and cured at 180°C for 120 minutes to obtain an absorbing honeycomb core, which includes 35 parts of honeycomb, 5 parts of absorbent, and 40 parts of resin.

[0053] (2) The wave-transmitting layer, the wave-absorbing honeycomb core obtained in the above step (1), the wave-absorbing layer and the reflective layer are bonded and cured from top to bottom by a structural adhesive film to obtain a wave-absorbing honeycomb core sandwich structure. The wave-transmitting layer is a quartz fiber reinforced cyanate ester composite material with a resin content of 38% and a thickness of 0.6 mm. The fiber matrix of the wave-absorbing layer is a quartz fiber reinforced bismaleimide resin composite material with a thickness of 2.4 mm, and the dispersed absorbent is an ultrafine iron-aluminum-silicon alloy powder with a particle size D90 of 8 μm. The components of the wave-absorbing layer are calculated by weight: 20 parts of resin, 20 parts of fiber, and 45 parts of absorbent. The reflective layer is a carbon fiber reinforced epoxy resin-based composite material with a resin content of 40% and a thickness of 0.4 mm.

[0054] Example 7

[0055] The hot-melt epoxy resin was dissolved in N, N-dimethylacetamide solvent, and Ni-plated hollow glass microspheres (the particle size D90 of the Ni-plated hollow glass microspheres was 10 μm, and the average thickness of the nickel layer on the surface of the hollow microspheres was 0.5 μm, as the absorbing material) were added, and mechanical stirring was performed for 60 minutes to obtain the absorbing resin glue solution; the glue solution was repeatedly coated and impregnated on an aramid paper honeycomb core with a thickness of 5 mm, and the core was weighed after drying until the target weight gain was reached; the impregnated aramid paper honeycomb core was placed in an oven and cured at 180°C for 120 minutes to obtain the absorbing honeycomb core, which includes 15 parts of honeycomb, 25 parts of absorbent, and 40 parts of resin.

[0056] (2) The wave-transmitting layer, the wave-absorbing honeycomb core obtained in the above step (1), the wave-absorbing layer and the reflective layer are bonded and cured from top to bottom by a structural adhesive film to obtain a wave-absorbing honeycomb core sandwich structure. The wave-transmitting layer is a quartz fiber reinforced cyanate ester composite material with a resin content of 38% and a thickness of 0.6 mm. The fiber matrix of the wave-absorbing layer is a quartz fiber reinforced bismaleimide resin composite material with a thickness of 2.4 mm, and the dispersed absorbent is an ultrafine iron-aluminum-silicon alloy powder with a particle size D90 of 8 μm. The components of the wave-absorbing layer are calculated by weight: 20 parts of resin, 20 parts of fiber, and 45 parts of absorbent. The reflective layer is a carbon fiber reinforced epoxy resin-based composite material with a resin content of 40% and a thickness of 0.4 mm.

[0057] Example 8

[0058] (1) A hot-melt epoxy resin is dissolved in N,N-dimethylacetamide solvent, and Ni-plated hollow glass microspheres (the particle size D90 of the Ni-plated hollow glass microspheres is 15 μm, and the average thickness of the nickel layer on the surface of the hollow microspheres is 0.5 μm, as a microwave absorbing material) are added, and mechanical stirring is performed for 60 minutes to obtain a microwave absorbing resin glue solution; the glue solution is repeatedly applied to an aramid paper honeycomb core with a thickness of 5 mm, and the core is weighed after drying until the target weight gain is reached; the impregnated aramid paper honeycomb core is placed in an oven and cured at 180°C for 120 minutes to obtain a microwave absorbing honeycomb core, wherein the microwave absorbing honeycomb core includes 30 parts of honeycomb, 10 parts of absorbing material, and 40 parts of resin.

[0059] (2) The wave-transmitting layer, the wave-absorbing honeycomb core obtained in the above step (1), the wave-absorbing layer and the reflective layer are bonded and cured from top to bottom by a structural adhesive film to obtain a wave-absorbing honeycomb core sandwich structure. The wave-transmitting layer is a quartz fiber reinforced cyanate ester composite material with a resin content of 38% and a thickness of 0.6 mm. The fiber matrix of the wave-absorbing layer is a quartz fiber reinforced bismaleimide resin composite material with a thickness of 2.4 mm, and the dispersed absorbent is an ultrafine iron-aluminum-silicon alloy powder with a particle size D90 of 8 μm. The components of the wave-absorbing layer are calculated by weight: 20 parts of resin, 20 parts of fiber, and 45 parts of absorbent. The reflective layer is a carbon fiber reinforced epoxy resin-based composite material with a resin content of 40% and a thickness of 0.4 mm.

[0060] Example 9

[0061] (1) A hot-melt epoxy resin is dissolved in N,N-dimethylacetamide solvent, and Ni-plated hollow glass microspheres (the particle size D90 of the Ni-plated hollow glass microspheres is 5 μm, and the average thickness of the nickel layer on the surface of the hollow microspheres is 0.5 μm, as a microwave absorbing material) are added, and mechanical stirring is performed for 60 minutes to obtain a microwave absorbing resin glue solution; the glue solution is repeatedly applied to an aramid paper honeycomb core with a thickness of 5 mm, and the core is weighed after drying until the target weight gain is reached; the impregnated aramid paper honeycomb core is placed in an oven and cured at 180°C for 120 minutes to obtain a microwave absorbing honeycomb core, which includes 30 parts of honeycomb, 10 parts of absorbing material, and 40 parts of resin.

[0062] (2) The wave-transmitting layer, the wave-absorbing honeycomb core obtained in the above step (1), the wave-absorbing layer and the reflective layer are bonded and cured from top to bottom by a structural adhesive film to obtain a wave-absorbing honeycomb core sandwich structure. The wave-transmitting layer is a quartz fiber reinforced cyanate ester composite material with a resin content of 38% and a thickness of 0.6 mm. The fiber matrix of the wave-absorbing layer is a quartz fiber reinforced bismaleimide resin composite material with a thickness of 2.4 mm, and the dispersed absorbent is an ultrafine iron-aluminum-silicon alloy powder with a particle size D90 of 8 μm. The components of the wave-absorbing layer are calculated by weight: 20 parts of resin, 20 parts of fiber, and 45 parts of absorbent. The reflective layer is a carbon fiber reinforced epoxy resin-based composite material with a resin content of 40% and a thickness of 0.4 mm.

[0063] Example 10

[0064] (1) A hot-melt epoxy resin is dissolved in N,N-dimethylacetamide solvent, and Ni-plated hollow glass microspheres (the particle size D90 of the Ni-plated hollow glass microspheres is 20 μm, and the average thickness of the nickel layer on the surface of the hollow microspheres is 0.5 μm, as a wave-absorbing material) are added, and mechanical stirring is performed for 60 minutes to obtain a wave-absorbing resin glue solution; the glue solution is repeatedly applied to an aramid paper honeycomb core with a thickness of 5 mm, and the core is weighed after drying until the target weight gain is reached; the impregnated aramid paper honeycomb core is placed in an oven and cured at 180°C for 120 minutes to obtain a wave-absorbing honeycomb core, wherein the wave-absorbing honeycomb core includes 30 parts of honeycomb, 10 parts of wave-absorbing material, and 40 parts of resin.

[0065] (2) The wave-transmitting layer, the wave-absorbing honeycomb core obtained in the above step (1), the wave-absorbing layer and the reflective layer are bonded and cured from top to bottom by a structural adhesive film to obtain a wave-absorbing honeycomb core sandwich structure. The wave-transmitting layer is a quartz fiber reinforced cyanate ester composite material with a resin content of 38% and a thickness of 0.6 mm. The fiber matrix of the wave-absorbing layer is a quartz fiber reinforced bismaleimide resin composite material with a thickness of 2.4 mm, and the dispersed absorbent is an ultrafine iron-aluminum-silicon alloy powder with a particle size D90 of 8 μm. The components of the wave-absorbing layer are calculated by weight: 20 parts of resin, 20 parts of fiber, and 45 parts of absorbent. The reflective layer is a carbon fiber reinforced epoxy resin-based composite material with a resin content of 40% and a thickness of 0.4 mm.

[0066] Embodiment 11

[0067] (1) A hot-melt epoxy resin is dissolved in N,N-dimethylacetamide solvent, and Ni-plated hollow glass microspheres (the particle size D90 of the Ni-plated hollow glass microspheres is 10 μm, and the average thickness of the nickel layer on the surface of the hollow microspheres is 0.02 μm, as a wave-absorbing material) are added, and mechanical stirring is performed for 60 minutes to obtain a wave-absorbing resin glue solution; the glue solution is repeatedly applied to an aramid paper honeycomb core with a thickness of 5 mm, and the core is weighed after drying until the target weight gain is reached; the impregnated aramid paper honeycomb core is placed in an oven and cured at 180°C for 120 minutes to obtain a wave-absorbing honeycomb core, wherein the wave-absorbing honeycomb core includes 30 parts of honeycomb, 10 parts of wave-absorbing material, and 40 parts of resin.

[0068] (2) The wave-transmitting layer, the wave-absorbing honeycomb core obtained in the above step (1), the wave-absorbing layer and the reflective layer are bonded and cured from top to bottom by a structural adhesive film to obtain a wave-absorbing honeycomb core sandwich structure. The wave-transmitting layer is a quartz fiber reinforced cyanate ester composite material with a resin content of 38% and a thickness of 0.6 mm. The fiber matrix of the wave-absorbing layer is a quartz fiber reinforced bismaleimide resin composite material with a thickness of 2.4 mm, and the dispersed absorbent is an ultrafine iron-aluminum-silicon alloy powder with a particle size D90 of 8 μm. The components of the wave-absorbing layer are calculated by weight: 20 parts of resin, 20 parts of fiber, and 45 parts of absorbent. The reflective layer is a carbon fiber reinforced epoxy resin-based composite material with a resin content of 40% and a thickness of 0.4 mm.

[0069] Example 12

[0070] (1) A hot-melt epoxy resin is dissolved in N,N-dimethylacetamide solvent, and Ni-plated hollow glass microspheres (the particle size D90 of the Ni-plated hollow glass microspheres is 10 μm, and the average thickness of the nickel layer on the surface of the hollow microspheres is 1 μm, as a microwave absorbing material) are added, and mechanical stirring is performed for 60 minutes to obtain a microwave absorbing resin glue solution; the glue solution is repeatedly applied to an aramid paper honeycomb core with a thickness of 5 mm, and the core is weighed after drying until the target weight gain is reached; the impregnated aramid paper honeycomb core is placed in an oven and cured at 180°C for 120 minutes to obtain a microwave absorbing honeycomb core, which includes 30 parts of honeycomb, 10 parts of absorbing material, and 40 parts of resin.

[0071] (2) The wave-transmitting layer, the wave-absorbing honeycomb core obtained in the above step (1), the wave-absorbing layer and the reflective layer are bonded and cured from top to bottom by a structural adhesive film to obtain a wave-absorbing honeycomb core sandwich structure. The wave-transmitting layer is a quartz fiber reinforced cyanate ester composite material with a resin content of 38% and a thickness of 0.6 mm. The fiber matrix of the wave-absorbing layer is a quartz fiber reinforced bismaleimide resin composite material with a thickness of 2.4 mm, and the dispersed absorbent is an ultrafine iron-aluminum-silicon alloy powder with a particle size D90 of 8 μm. The components of the wave-absorbing layer are calculated by weight: 20 parts of resin, 20 parts of fiber, and 45 parts of absorbent. The reflective layer is a carbon fiber reinforced epoxy resin-based composite material with a resin content of 40% and a thickness of 0.4 mm.

[0072] Embodiment 13

[0073] (1) A hot-melt epoxy resin is dissolved in N,N-dimethylacetamide solvent, and Ni-plated hollow glass microspheres (the particle size D90 of the Ni-plated hollow glass microspheres is 10 μm, and the average thickness of the nickel layer on the surface of the hollow microspheres is 1.5 μm, as a wave-absorbing material) are added, and mechanical stirring is performed for 60 minutes to obtain a wave-absorbing resin glue solution; the glue solution is repeatedly applied to an aramid paper honeycomb core with a thickness of 5 mm, and the core is weighed after drying until the target weight gain is reached; the impregnated aramid paper honeycomb core is placed in an oven and cured at 180°C for 120 minutes to obtain a wave-absorbing honeycomb core, wherein the wave-absorbing honeycomb core includes 30 parts of honeycomb, 10 parts of wave-absorbing material, and 40 parts of resin.

[0074] (2) The wave-transmitting layer, the wave-absorbing honeycomb core obtained in the above step (1), the wave-absorbing layer and the reflective layer are bonded and cured from top to bottom by a structural adhesive film to obtain a wave-absorbing honeycomb core sandwich structure. The wave-transmitting layer is a quartz fiber reinforced cyanate ester composite material with a resin content of 38% and a thickness of 0.6 mm. The fiber matrix of the wave-absorbing layer is a quartz fiber reinforced bismaleimide resin composite material with a thickness of 2.4 mm, and the dispersed absorbent is an ultrafine iron-aluminum-silicon alloy powder with a particle size D90 of 8 μm. The components of the wave-absorbing layer are calculated by weight: 20 parts of resin, 20 parts of fiber, and 45 parts of absorbent. The reflective layer is a carbon fiber reinforced epoxy resin-based composite material with a resin content of 40% and a thickness of 0.4 mm.

[0075] Embodiment 14

[0076] (1) A hot-melt epoxy resin is dissolved in N,N-dimethylacetamide solvent, and Ni-plated hollow glass microspheres (the particle size D90 of the Ni-plated hollow glass microspheres is 10 μm, and the average thickness of the nickel layer on the surface of the hollow microspheres is 0.5 μm, as a microwave absorbing material) are added, and mechanical stirring is performed for 60 minutes to obtain a microwave absorbing resin glue solution; the glue solution is repeatedly applied to an aramid paper honeycomb core with a thickness of 5 mm, and the core is weighed after drying until the target weight gain is reached; the impregnated aramid paper honeycomb core is placed in an oven and cured at 180°C for 120 minutes to obtain a microwave absorbing honeycomb core, which includes 30 parts of honeycomb, 10 parts of absorbing material, and 40 parts of resin.

[0077] (2) The wave-transmitting layer, the wave-absorbing honeycomb core obtained in step (1) and the reflective layer are bonded and cured from top to bottom by a structural adhesive film to obtain a wave-absorbing honeycomb core sandwich structure. The wave-transmitting layer is a quartz fiber reinforced cyanate ester composite material with a resin content of 38% and a thickness of 0.6 mm. The reflective layer is a carbon fiber reinforced epoxy resin-based composite material with a resin content of 40% and a thickness of 0.4 mm.

[0078] Comparative Example 1

[0079] (1) A hot-melt epoxy resin is dissolved in N,N-dimethylacetamide solvent, superconductive carbon black (D90 is 25 nm, resistivity is 0.3 Ω·m, as an absorbing material) is added, and mechanical stirring is performed for 60 min to obtain an absorbing resin glue solution; the glue solution is repeatedly applied to an aramid paper honeycomb core with a thickness of 5 mm, and the core is weighed after drying until the target weight gain is reached; the impregnated aramid paper honeycomb core is placed in an oven and cured at 180°C for 120 min to obtain an absorbing honeycomb core, wherein the absorbing honeycomb core comprises 30 parts of honeycomb, 10 parts of absorbing material, and 40 parts of resin.

[0080] (2) The wave-transmitting layer, the wave-absorbing honeycomb core obtained in the above step (1), the wave-absorbing layer and the reflective layer are bonded and cured from top to bottom by a structural adhesive film to obtain a wave-absorbing honeycomb core sandwich structure. The wave-transmitting layer is a quartz fiber reinforced cyanate ester composite material with a resin content of 38% and a thickness of 0.6 mm. The fiber matrix of the wave-absorbing layer is a quartz fiber reinforced bismaleimide resin composite material with a thickness of 2.4 mm, and the dispersed absorbent is an ultrafine iron-aluminum-silicon alloy powder with a particle size D90 of 8 μm. The components of the wave-absorbing layer are calculated by weight: 20 parts of resin, 20 parts of fiber, and 45 parts of absorbent. The reflective layer is a carbon fiber reinforced epoxy resin-based composite material with a resin content of 40% and a thickness of 0.4 mm.

[0081] Comparative Example 2

[0082] (1) A hot-melt epoxy resin was dissolved in N,N-dimethylacetamide solvent, carbonyl iron powder (D90 was 10 μm, used as an absorbing material) was added, and mechanical stirring was performed for 60 min to obtain an absorbing resin glue solution; the glue solution was repeatedly applied to an aramid paper honeycomb core with a thickness of 5 mm, and the core was weighed after drying until the target weight gain was reached; the impregnated aramid paper honeycomb core was placed in an oven and cured at 180°C for 120 min to obtain an absorbing honeycomb core, wherein the absorbing honeycomb core comprises 30 parts of honeycomb, 10 parts of absorbing material, and 40 parts of resin.

[0083] (2) The wave-transmitting layer, the wave-absorbing honeycomb core obtained in the above step (1), the wave-absorbing layer and the reflective layer are bonded and cured from top to bottom by a structural adhesive film to obtain a wave-absorbing honeycomb core sandwich structure. The wave-transmitting layer is a quartz fiber reinforced cyanate ester composite material with a resin content of 38% and a thickness of 0.6 mm. The fiber matrix of the wave-absorbing layer is a quartz fiber reinforced bismaleimide resin composite material with a thickness of 2.4 mm, and the dispersed absorbent is an ultrafine iron-aluminum-silicon alloy powder with a particle size D90 of 8 μm. The components of the wave-absorbing layer are calculated by weight: 20 parts of resin, 20 parts of fiber, and 45 parts of absorbent. The reflective layer is a carbon fiber reinforced epoxy resin-based composite material with a resin content of 40% and a thickness of 0.4 mm.

[0084] Testing the wave absorption performance

[0085] The absorbing honeycomb core sandwich structures prepared in the above examples and comparative examples were tested for absorbing performance with reference to the GJB 2038A-2011 radar absorbing material reflectivity test method, wherein the sample size was 300*300 mm and the frequency was 2-18 GHz.

[0086] The test results are shown in Table 1.

[0087] Table 1

[0088] Attenuation peak frequency (GHz) Attenuation peak(db) Attenuation 10db bandwidth (GHz) Example 1 6.2 -24.8 3.2 Example 2 4.8 -32.1 4.8 Example 3 3.9 -35.0 5.4 Example 4 5.2 -30.8 4.1 Example 5 6.0 -26.8 3.4 Example 6 9.3 -14.2 1.7 Example 7 8.4 -20.5 2.3 Example 8 6.4 -21.5 3.0 Example 9 6.6 -22.3 3.1 Example 10 7.9 -18.7 2.4 Embodiment 11 6.3 -23.9 3.3 Example 12 7.1 -19.3 2.4 Embodiment 13 8.3 -14.4 2.0 Embodiment 14 11.4 -11.9 1.2 Comparative Example 1 10.4 -12.9 1.5 Comparative Example 2 11.8 -11.9 1.3

[0089] From the above description, it can be seen that the above embodiments of the present invention achieve the following technical effects:

[0090] The present application uses metallized hollow glass microspheres to replace the dielectric materials and ferromagnetic materials commonly used in the prior art for honeycomb core materials as wave absorbers. Metal-coated hollow glass microspheres have the advantages of low density and large specific surface area, and loading the metal on the surface of the hollow glass microspheres can effectively reduce the skin effect caused by the metal material, overcome the defect of weak absorption of high-frequency electromagnetic waves, and effectively improve the magnetic loss, thereby effectively improving the low-frequency wave absorption performance. At the same time, after the metal layer is coated on the hollow glass microspheres as an absorbing material, when the absorbing material is loaded on the honeycomb substrate, the sedimentation of the metal is effectively avoided, and the effect of being distributed as evenly as possible on the honeycomb carrier is achieved. In summary, the absorbing honeycomb core material of the present application utilizes evenly distributed absorbing materials and honeycomb carriers to achieve simultaneous absorption of low-frequency waves and high-frequency waves.

[0091] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A wave-absorbing honeycomb core material, comprising a honeycomb matrix, a resin bonding portion and a wave-absorbing material, wherein the resin bonding portion fixes the wave-absorbing material on the honeycomb matrix, characterized in that: The absorbing material is surface metallized hollow glass microspheres; the surface metallized hollow glass microspheres are selected from any one or more of Ni-plated hollow glass microspheres, Fe-plated hollow glass microspheres, and Co-plated hollow glass microspheres, and the coating thickness of the surface metallized hollow glass microspheres is 0.02-0.9 μm; the D90 of the absorbing material is between 5-15 μm; in the absorbing honeycomb core material, the weight ratio of the honeycomb matrix, the resin bonding part and the absorbing material is 20-40:30-50:10-20.

2. The wave-absorbing honeycomb core material according to claim 1, characterized in that: The resin bonding part is formed by curing one or more of hot-melt epoxy resin, hot-melt phenolic resin or hot-melt bismaleimide resin.

3. The wave-absorbing honeycomb core material according to claim 1, characterized in that: The honeycomb matrix is ​​an aramid paper honeycomb.

4. A wave-absorbing honeycomb core sandwich structure, comprising a wave-transmitting layer, a wave-absorbing honeycomb core layer and a reflective layer bonded in sequence, characterized in that: The wave-absorbing honeycomb core layer is the wave-absorbing honeycomb core material according to any one of claims 1 to 3, and the thickness of the wave-absorbing honeycomb core layer is 5 to 20 mm.

5. The microwave-absorbing honeycomb core sandwich structure according to claim 4, characterized in that: The thickness of the wave-transmitting layer is 0.2-1.0 mm, and the wave-transmitting layer includes a first fiber matrix and a first resin loaded on the first fiber matrix. The weight content of the first resin in the wave-transmitting layer is 33%-45%, the fiber matrix is ​​quartz fiber or glass fiber, and the first resin is epoxy resin or cyanate ester.

6. The microwave-absorbing honeycomb core sandwich structure according to claim 4, characterized in that: The absorbing honeycomb core sandwich structure also includes an absorbing layer bonded between the absorbing honeycomb core layer and the reflecting layer, the absorbing layer includes a second fiber matrix, a second resin loaded on the second fiber matrix, and an absorbing agent, and the weight ratio of the second fiber matrix, the second resin and the absorbing agent is 15~30:15~30:40~70.

7. The microwave-absorbing honeycomb core sandwich structure according to claim 6, characterized in that: Includes at least one of the following features: (1) The thickness of the absorbing layer is 1.0~3.0mm; (2) The second resin is a hot-melt epoxy resin or a bismaleimide resin; (3) The second fiber matrix is ​​quartz fiber or aramid fiber; (4) The absorber is a magnetic medium type absorber, the D90 of the magnetic medium type absorber is between 1 and 10 μm, and the magnetic medium type absorber includes any one or more of ferrite, carbonyl iron powder and ultrafine metal powder.

8. The microwave-absorbing honeycomb core sandwich structure according to claim 4, characterized in that: The thickness of the reflective layer is 0.2-0.6 mm. The reflective layer comprises carbon fibers and epoxy resin loaded on the carbon fibers. The weight content of the epoxy resin in the reflective layer is 33-50%.

Citation Information

Patent Citations

  • Radar wave absorbing agent and preparation method employing chemical plating technique

    CN101294055A

  • Double-layer skin wave-absorbing honeycomb sandwich structure and preparation method thereof

    CN111186201A